2017
DOI: 10.1159/000477319
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA AFAP1-AS1 Promoted Tumor Growth and Invasion in Cholangiocarcinoma

Abstract: Background: Long non-coding RNAs (lncRNAs) have been shown to play important roles in a wide range of pathophysiological processes, including cancer progression. Our previous study has shown that AFAP1-AS1 was upregulated and acted as an oncogene in hepatocellular carcinoma. However, the expression and biological functions of lncRNA AFAP1-AS1 in intrahepatic cholangiocarcinoma (CCA) remains largely unknown. Methods: The expression level of AFAP1-AS1 was measured in 56 pairs of human cholangiocarcinoma tumor ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Studies have shown that aberrant lncRNA expression influences cancer progression and can predict patient outcome [12, 24]. In the present study, we examined the expression of SNHG12 in cervical cancer tissues, compared to the corresponding normal tissues, and we found that SNHG12 was significantly upregulated in cervical cancer tissue and that high SNHG12 was positively associated with FIGO stage, lymph node metastasis and a poor prognosis.…”
Section: Discussionmentioning
confidence: 69%
“…Studies have shown that aberrant lncRNA expression influences cancer progression and can predict patient outcome [12, 24]. In the present study, we examined the expression of SNHG12 in cervical cancer tissues, compared to the corresponding normal tissues, and we found that SNHG12 was significantly upregulated in cervical cancer tissue and that high SNHG12 was positively associated with FIGO stage, lymph node metastasis and a poor prognosis.…”
Section: Discussionmentioning
confidence: 69%
“…Nowadays, numerous lncRNAs have been reported to play important role in carcinogenesis at both transcriptional and post-transcriptional levels, but their specific mechanisms of action still remain elusive [5, 18, 19, 20]. H19 has been identified as one of the lncRNAs involved in tumorigenesis, however, its role in tumor proliferation and apoptosis has been a subject of controversy for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…30,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In this review, the related clinicopathological characteristics and molecular functions of this lncRNA in cancers are presented in Tables 1 and 2.…”
Section: Identification Of Afap1-as1mentioning
confidence: 99%